Blockade of LAG3 enhances responses of tumor-infiltrating T cells in mismatch repair-proficient liver metastases of colorectal cancer. (3rd July 2018) - Zhou, Guoying; Noordam, Lisanne; Sprengers, Dave; Doukas, Michail; Boor, Patrick P. C.; van Beek, Adriaan A.; Erkens, Remco; Mancham, Shanta; Grünhagen, Dirk; Menon, Anand G.; Lange, Johan F.; Burger, Pim J. W. A.; et al.
ABSTRACT: Purpose : Liver metastasis develops in >50% of patients with colorectal cancer (CRC), and is a leading cause of CRC-related mortality. We aimed to identify which inhibitory immune checkpoint pathways can be targeted to enhance functionality of intra-tumoral T-cells in mismatch repair-proficient liver metastases of colorectal cancer (LM-CRC). Methodology : Intra-tumoral expression of multiple inhibitory molecules was compared among mismatch repair-proficient LM-CRC, peritoneal metastases of colorectal cancer (PM-CRC) and primary CRC. Expression of inhibitory molecules was also analyzed on leukocytes isolated from paired resected metastatic liver tumors, tumor-free liver tissues, and blood of patients with mismatch repair-proficient LM-CRC. The effects of blocking inhibitory pathways on tumor-infiltrating T-cell responses were studied in ex vivo functional assays. Results : Mismatch repair-proficient LM-CRC showed higher expression of inhibitory receptors on intra-tumoral T-cells and contained higher proportions of CD8 + T-cells, dendritic cells and monocytes than mismatch repair-proficient primary CRC and/or PM-CRC. Inhibitory receptors LAG3, PD-1, TIM3 and CTLA4 were higher expressed on CD8 + T-cells, CD4 + T-helper and/or regulatory T-cells in LM-CRC tumors compared with tumor-free liver and blood. Antibody blockade of LAG3 or PD-L1 increased proliferation and effector cytokine production of intra-tumoral T-cells isolated from LM-CRC in response to both polyclonal and autologous tumor-specific stimulations. Higher LAG3 expression on intra-tumoral CD8 + T-cells associated with longer progression-free survival of LM-CRC patients. Conclusion : Mismatch repair-proficient LM-CRC may be more sensitive to immune checkpoint inhibitors than mismatch repair-proficient primary CRC. Blocking LAG3 enhances tumor-infiltrating T-cell responses of mismatch repair-proficient LM-CRC, and therefore may be a new promising immunotherapeutic target for LM-CRC.